Spatiotemporal Differentiation and Influencing Factors of Urban Land Green Use Efficiency in Jiangsu Province from Perspective of High-quality Development - Yuhao Feng; Wen Tong; Zijie Li; Haidi Zhu; Qun Wu (Shuitu baochi tongbao)
[Objective] The spatiotemporal differentiation and influencing factors of urban land green use efficiency in Jiangsu Province were quantitatively analyzed based on an exploration of the connotation of urban land green use efficiency from the perspective of high-quality development in order to provide a scientific reference for increasing urban land green use efficiency. [Methods] The Super-SBM-Undesirable model, GIS spatial analysis, and panel data model were applied to investigate the regional disparity and evolution characteristics of urban land green use efficiency in Jiangsu Province from 2008 to 2020. The impact on the green use efficiency of urban land was examined from the three aspects of "decentralization, greening, and globalization". [Results] ① The green use efficiency of urban land in Jiangsu Province was at a relatively high level. Most cities showed a downward trend before 2018 and an upturn after 2018. The overall spatial distribution could be characterized as "low in the north and high in the south, low in the west and high in the east". ② The fluctuation difference of urban land green use efficiency was obvious in Jiangsu Province. Urban land green use efficiency in northern and central Jiangsu Province increased first and then decreased, while in southern Jiangsu urban land green use efficiency decreased first and then increased. ③ Forest coverage rate, park green space area, foreign direct investment, and industrial structure promoted green use efficiency of urban land, while the level of urban development produced a U-shaped nonlinear effect on green use efficiency. Financial pressure was the main contributor to the decrease in green use efficiency of urban land. [Conclusion] In the future, it will be necessary to advocate for the creation of high-quality development models and formulate different optimization and adjustment measures in different regions based on strengthening regional integration, promoting the transformation and upgrading of local industrial structure, and changing the mode of economic development in order to improve the green utilization efficiency of urban land in Jiangsu Province.